Compressive crushing of novel aluminum hexagonal honeycombs with perforations: Experimental and numerical investigations. (November 2017) - Wang, Zhengjin; Qin, Qinghua; Chen, Shangjun; Yu, Xuehui; Li, Huimin; Wang, T.J.
Abstract: The quasi-static compressive behavior of novel aluminum hexagonal honeycombs with perforations on the cell wall is investigated experimentally and numerically. Compressive experiments on the perforated honeycombs with different cell numbers are conducted to study the effect of specimen sizes. The measured collapse stress is almost insensitive to the specimen sizes, while the crushing stress increases with the cell numbers and finally converges to a stable plateau for the specimens beyond 15 × 15 cells. Finite element simulations are performed to study the effects of perforation size, spacing and shape on the mechanical properties of honeycombs. The results reveal that perforation size is a key parameter that affects the compressive mechanical properties and deformation patterns of honeycombs. The perforation number along the height direction of a cell has nearly no influence on the collapse stress, and only affect the crushing stress when the perforation size is large. The perforation shape impacts the collapse of honeycombs but has minor effect on the subsequent crushing stage.